2007
DOI: 10.1063/1.2803898
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the (HI)2 photodissociation dynamics through a nonadiabatic wave packet study of the I*–HI complex

Abstract: The nonadiabatic photodissociation dynamics of (HI)2 is simulated by applying a wave packet approach which starts from the I*-HI complex (where I* denotes the I(2P1/2) excited electronic state) produced after the photodissociation of the first HI moiety within (HI)2. In the model, two excited electronic potential surfaces corresponding to I*-HI(A 1Pi1) and I-HI(A 1Pi1), which interact through spin-rotation coupling, are considered. The simulations show that upon photodissociation of HI within I*-HI, the dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Wave packet simulations of the (HI) 2 nonadiabatic photodissociation were reported recently, , and they confirmed the mechanism proposed in ref to explain the appearance of the β peak in the H fragment spectrum. The model applied in the simulations took advantage of the sequential character of the (HI) 2 photodissociation dynamics.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Wave packet simulations of the (HI) 2 nonadiabatic photodissociation were reported recently, , and they confirmed the mechanism proposed in ref to explain the appearance of the β peak in the H fragment spectrum. The model applied in the simulations took advantage of the sequential character of the (HI) 2 photodissociation dynamics.…”
Section: Introductionsupporting
confidence: 81%
“…The calculated β peak accounted for 0.15% of the H-fragment kinetic energy distribution, in good qualitative agreement with the experimental estimate of 0.1−1% for the signal of this peak . The simulations indeed showed that the β peak is produced by nonadiabatic transitions induced by relatively weak intracluster collisions within the I*−HI complex, between the nascent H fragment and I*, which lead to deactivation of I* . A most interesting result of the distribution calculated for excitation with 266 nm radiation was the finding of a high probability of bound I 2 product fragments in highly excited rovibrational states.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…(2) d.e by the modulous d of d, which amounts to suppose that d is parallel to e at the instant of the photon absorption. This approximation appears to be very satisfying provided than one is not interested in vector properties [6,26,30,[41][42][43]. d is either parallel or perpendicular to the triatomic plane and d does only depend on the configuration of ABC, i.e., d ≡ d(R, r, θ).…”
Section: Quantum Partial Cross Section and Product State Distributionmentioning
confidence: 99%
“…9 Assuming the electronic problem of a process under scrutiny has been solved by the usual methods of quantum chemistry [10][11][12] and the potential energy surfaces (PESs) involved in the process are available as well as their possible nonadiabatic couplings, state-of-the-art descriptions of its dynamics are performed within the framework of rigorous quantum treatments of nuclear motions. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] More often than not, however, these treatments can hardly be applied to polyatomic processes involving more than three atoms, for the basis sizes necessary to converge the calculations may either be prohibitive, or require computation times of several months. a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%